2005
DOI: 10.1007/11531371_28
|View full text |Cite
|
Sign up to set email alerts
|

Light-Weight Distributed Web Interfaces: Preparing the Web for Heterogeneous Environments

Abstract: Abstract. In this paper we show an approach that allows web interfaces to be dynamically distributed among several interconnected heterogeneous devices in an environment to support the tasks and activities the user performs. The approach uses a light-weight HTTP-based daemon as a distribution manager and RelaxNG schemas to describe the service user interfaces offered by native applications. From these service descriptions, the XHTML-based user interface is generated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Concerning DUI in conjunction with the WA and EUD fields, and as pointed out in [14], we can appreciate that it is not easy to provide DUI for existing and third party Web content, although some approaches have tackled isolated specific dimensions, specifically involving end-users. User-Driven DUI was previously defined in [15]; however, although this approach does not consider third-party existing Web sites as potential targets, other approaches do. For instance, [7] lets users to annotate some parts of exiting Web UI in order to migrate components under user demand.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Concerning DUI in conjunction with the WA and EUD fields, and as pointed out in [14], we can appreciate that it is not easy to provide DUI for existing and third party Web content, although some approaches have tackled isolated specific dimensions, specifically involving end-users. User-Driven DUI was previously defined in [15]; however, although this approach does not consider third-party existing Web sites as potential targets, other approaches do. For instance, [7] lets users to annotate some parts of exiting Web UI in order to migrate components under user demand.…”
Section: Background and Related Workmentioning
confidence: 99%
“…If another user or platform comes in the context of use, it is hard to replicate or migrate on this platform the part that has already been transferred to the first smartphone. In Lightweight services [36], once a service has been selected, it can be distributed to any platform, existing or arriving, but a service can be distributed only once. On the one hand, this does not create any conflict, but on the other hand, it does not support replication.…”
Section: Shortcomings Of Related Workmentioning
confidence: 99%
“…DUIs have been successfully used in various domains of human activity (e.g., ambient intelligence [22,23], clinical systems [5], economics [14]) and in computer science (e.g., migratory UIs [3,6,25,39], service-oriented architecture [36], ubiquitous computing [7]). DUIs are fundamental because several applications require the integration of distributed interaction devices as functional wholes.…”
Section: Introductionmentioning
confidence: 99%
“…This type of suppport for distributed user interfaces is required to deploy a user interface for an ambient intelligent environment. In Vandervelpen et al (2005) we show how conventional interactive websites can be distributed among different interaction resources with a minimum of effort required from the designer to prepare the website for distribution. This proves a structured high-level user interface description language (HTML in the case of the website) is the most suitable way to create distributable user interfaces.…”
Section: Related Workmentioning
confidence: 99%
“…In Vandervelpen et al (2005) we showed a method that uses XHTML as the presentation language and a set of rules and a cost function to select the "preferred" distribution configuration among all possible configurations. The XHTML document was subdivided according the tasks it supported, and the different parts were distributed among the available devices in the neighborhood of the user.…”
Section: Task Representationsmentioning
confidence: 99%